Structural analysis of Bacillus subtilis 168 endospore peptidoglycan and its role during differentiation. - Atrih, A (1996)
The structure of the endospore cell wall peptidoglycan of Bacillus subtilis has been examined. Spore peptidoglycan was produced by the development of a method based on chemical permeabilization of the spore coats and enzymatic hydrolysis of the peptidoglycan. The resulting muropeptides which were >97% pure were analyzed by reverse-phase high-performance liquid chromatography, amino acid analysis, and mass spectrometry. This revealed that 49% of the muramic acid residues in the glycan backbone were present in the delta-lactam form which occurred predominantly every second muramic acid. The glycosidic bonds adjacent to the muramic acid delta-lactam residues were resistant to the action of muramidases. Of the muramic acid residues, 25.7 and 23.3% were substituted with a tetrapeptide and a single L-alanine, respectively. Only 2% of the muramic acids had tripeptide side chains and may constitute the primordial cell wall, the remainder of the peptidoglycan being spore cortex. The spore peptidoglycan is very loosely cross-linked at only 2.9% of the muramic acid residues, a figure approximately 11-fold less than that of the vegetative cell wall. The peptidoglycan from strain AA110 (dacB) had fivefold-greater cross-linking (14.4%) than the wild type and an altered ratio of muramic acid substituents having 37.0, 46.3, and 12.3% delta-lactam, tetrapeptide, and single L-alanine, respectively. This suggests a role for the DacB protein (penicillin-binding protein 5*) in cortex biosynthesis. The sporulation-specific putative peptidoglycan hydrolase CwlD plays a pivotal role in the establishment of the mature spore cortex structure since strain AA107 (cwlD) has spore peptidoglycan which is completely devoid of muramic acid delta-lactam residues. Despite this drastic change in peptidoglycan structure, the spores are still stable but are unable to germinate. The role of delta-lactam and other spore peptidoglycan structural features in the maintenance of dormancy, heat resistance, and germination is discussed.